Common Fixed Point Theorems For Occasionally Weakly Compatible Mappings In Semi-Metric Space - Gupta, Neelmani (International Journal of Psychosocial Rehabilitation, 2010)
In this paper, we establish a common fixed point theorem for three pairs of self mappings in semi-metric space for occasionally weakly compatible mappings which improves and extends similar known results in the literature.